Method for producing separation membrane, separation membrane produced by said method, and electrochemical device including said separation membrane
Patent Information
- Application Number
- JP2024547738
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-10
- Filing Date
- 2023-02-10
- Publication Date
- 2025-02-28
AI Technical Summary
【0027】 本発明の一具現例によるポリオレフィン分離膜の製造方法は、ポリオレフィン分離膜に界面活性剤を導入することで、電解液の濡れ性が向上した分離膜を提供することができる。また、水シミによる外観不良を抑制することができ、優れた物性を有する分離膜、及び該分離膜を備える電気化学素子を提供することができる。
Smart Images

Figure 2025505754000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a separator that can be used in electrochemical devices such as lithium secondary batteries, a method for producing the separator, and an electrochemical device including the separator.
[0002] This application claims priority to Korean Patent Application No. 10-2022-0017777, filed on February 10, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]
[0003] Recently, interest in energy storage technology has been increasing. Applications of energy storage technology have expanded to include energy sources for mobile phones, camcorders, and laptops, as well as electric vehicles, and research and development efforts into electrochemical devices have been gradually realized. In this regard, electrochemical devices are the field that has attracted the most attention, and among them, rechargeable secondary batteries and lithium secondary batteries with high energy density have attracted attention.
[0004] A lithium secondary battery has a structure in which an electrode assembly having a separator interposed between a positive electrode and a negative electrode, each of which has an active material applied to an electrode current collector, is impregnated with a non-aqueous electrolyte containing a lithium salt.
[0005] In general, a lithium secondary battery is assembled by manufacturing an electrode assembly having a structure in which positive and negative electrodes are alternately stacked and a separator is interposed between the positive and negative electrodes, inserting the electrode assembly into a battery case such as a can or pouch of a certain size and shape, and finally injecting an electrolyte. At this time, the electrolyte seeps into the space between the positive electrode, negative electrode, and separator by capillary force. However, since the positive electrode, negative electrode, and separator are all highly hydrophobic materials while the electrolyte is a hydrophilic material due to the characteristics of the materials, it takes a considerable amount of time and requires complex process conditions to increase the wettability of the electrolyte to the electrodes and separator.
[0006] In particular, attempts have been made to control the pore size and porosity of the separator in order to improve the wettability of the electrolyte to the separator. A polymeric porous support using a polyolefin polymer resin is widely used as the separator, and although attempts have been made to control the pore size and porosity during the manufacture of the polymeric porous support separator, there is a limit to the improvement of the electrolyte wettability to the separator by physical methods. Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a method for producing a polyolefin separation membrane having improved wettability with an electrolyte.
[0008] Another object of the present invention is to provide a separator that has improved wettability with an electrolyte, suppresses defects in appearance, and has excellent physical properties, and an electrochemical device including the separator.
[0009] It will be readily apparent that other objects and advantages of the present invention can be realized by the means or methods recited in the claims and combinations thereof. [Means for solving the problem]
[0010] The present inventors have found that the above-mentioned problems can be solved by the following method for producing a separator, a separator produced by the method, and an electrochemical device including the separator.
[0011] The first embodiment is (S1) mixing and extruding a polyolefin and a diluent to prepare a polyolefin composition; (S2) forming and stretching the polyolefin composition into a sheet; (S3) immersing the stretched sheet in an extraction bath to produce a porous membrane; (S4) heat fixing the porous membrane; The extraction tank contains an organic solvent in a lower layer and water and a surfactant in an upper layer, in the method for producing a polyolefin separation membrane.
[0012] The second embodiment is the same as the first embodiment, The present invention relates to a method for producing a polyolefin separation membrane, wherein the surfactant has a transmittance change rate of 70% or less, and the transmittance change rate is defined by the following mathematical formula 1:
[0013] Permeability change rate (%) = [(Permeability before electrolyte storage - Permeability after electrolyte storage) / (Permeability before electrolyte storage)] × 100 ... Formula 1
[0014] (In Equation 1, the permeability before storage of the electrolyte means the permeability measured immediately after adding a surfactant to the electrolyte, and the permeability after storage of the electrolyte means the permeability after adding a surfactant to the electrolyte and storing it at 70° C. for 3 hours. The electrolyte is a mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 7:3, and LiPF 6 The surfactant is added in an amount of 1% by mass to 100% by mass of the electrolyte, and the transmittance of the electrolyte before and after storage is measured using an ultraviolet-visible spectrophotometer in accordance with ASTM-D1003.
[0015] The third embodiment is the first or second embodiment, The present invention relates to a method for producing a polyolefin separation membrane, in which the surfactant has a permeability change rate of 50% or less.
[0016] The fourth embodiment is any one of the first to third embodiments, The present invention relates to a method for producing a polyolefin separation membrane, wherein a weight ratio of the water to the surfactant is 99.9:0.1 to 95:5.
[0017] The fifth embodiment is any one of the first to fourth embodiments, The present invention relates to a method for producing a polyolefin separation membrane, wherein the organic solvent is methylene chloride (MC).
[0018] The sixth embodiment is any one of the first to fifth embodiments, In step (S3), the stretched sheet is passed through a lower layer portion first and then an upper layer portion in the extraction tank.
[0019] The seventh embodiment relates to a polyolefin separation membrane manufactured by the manufacturing method of any one of the first to sixth embodiments.
[0020] The eighth embodiment of the present invention provides a polyolefin porous support including a plurality of fibrils and a plurality of pores formed by the entanglement of the fibrils, The surfactant is included on the surface of the fibrils, The surfactant has a permeability change rate before and after storage of an electrolyte of 70% or less, and the permeability change rate is defined by the following Equation 1.
[0021] Permeability change rate (%) = [(Permeability before electrolyte storage - Permeability after electrolyte storage) / (Permeability before electrolyte storage)] × 100 ... Formula 1
[0022] (In Equation 1, the permeability before storage of the electrolyte means the permeability measured immediately after adding a surfactant to the electrolyte, and the permeability after storage of the electrolyte means the permeability after adding a surfactant to the electrolyte and storing it at 70° C. for 3 hours. The electrolyte is a mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 7:3, and LiPF 6 The surfactant is added in an amount of 1% by mass in 100% by mass of the electrolyte, and the transmittance of the electrolyte before and after storage is measured using a haze meter in accordance with ASTM-D1003.
[0023] The ninth embodiment is the eighth embodiment, The present invention relates to a polyolefin separation membrane in which the surfactant has a permeability change rate before and after storage of an electrolyte of 50% or less.
[0024] The tenth embodiment is the eighth or ninth embodiment, The polyolefin separation membrane has a water contact angle of 100° or less.
[0025] An eleventh embodiment relates to an electrochemical device including a positive electrode, a negative electrode, and a separator according to any one of the eighth to tenth embodiments interposed between the positive electrode and the negative electrode.
[0026] The twelfth embodiment is the eleventh embodiment, The present invention relates to an electrochemical device, wherein the electrochemical device is a lithium secondary battery. Effect of the Invention
[0027] According to an embodiment of the present invention, a method for manufacturing a polyolefin separator may provide a separator having improved wettability with an electrolyte by introducing a surfactant into the polyolefin separator, and may provide a separator having excellent physical properties and an electrochemical device including the separator, which may prevent poor appearance due to water stains.
[0028] In addition, according to one embodiment of the present invention, by including a surfactant in an extraction tank for extracting a diluent, a separate additional process for introducing the surfactant is not required, and therefore the surfactant can be introduced in a simpler manner.
[0029] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to further understand the technical ideas of the present invention as well as the contents of the invention, and therefore the present invention should not be interpreted as being limited to only the matters described in the drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]
[0030] [Figure 1]This is an image taken 5 minutes after 2 μl of propylene carbonate was dropped onto the surface of the separation membrane prepared in Example 1. [Diagram 2] This is an image taken 5 minutes after 2 μl of propylene carbonate was dropped onto the surface of the separation membrane prepared in Example 2. [Diagram 3] This is an image taken 5 minutes after 2 μl of propylene carbonate was dropped onto the surface of the separation membrane prepared in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The present invention will be described in detail below. The terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary and dictionary meanings, but should be interpreted as having meanings and concepts that correspond to the technical ideas of the present invention, based on the principle that the inventor himself can appropriately define the concepts of terms in order to best describe the invention.
[0032] Throughout this specification, when a part "includes" or "comprises" another element, it means that the part may further include the other element, not excluding the other element, unless otherwise specified.
[0033] In general, polyolefin-based separators are hydrophobic. Therefore, there is a problem that the electrolyte, which is hydrophilic, cannot be sufficiently impregnated into the polyolefin-based separator. Attempts have been made to improve the wettability of the electrolyte to the separator by controlling the pore size and porosity of the separator, but there are limitations to the physical control methods.
[0034] In order to solve this problem, the present inventors attempt to improve the wettability of the separator with the electrolyte by introducing a surfactant onto the surface of the separator during the manufacturing process of the separator.
[0035] Furthermore, the present inventors aim to provide a separator that can maintain stability even after an electrolyte is injected into an electrode assembly by introducing a predetermined surfactant onto the surface of the separator.
[0036] According to an embodiment of the present invention, a method for producing a separation membrane includes the steps of: (S1) mixing and extruding a polyolefin and a diluent to prepare a polyolefin composition; (S2) forming and stretching the polyolefin composition into a sheet; (S3) immersing the stretched sheet in an extraction bath to produce a porous membrane; (S4) heat fixing the porous membrane; The extraction tank contains an organic solvent in a lower layer and water and a surfactant in an upper layer.
[0037] In step (S1), a polyolefin composition is prepared by mixing a polyolefin and a diluent and extruding the mixture.
[0038] The polyolefin may be polyethylene; polypropylene; polybutylene; polypentene; polyhexene; polyoctene; a copolymer of two or more of ethylene, propylene, butene, pentene, 4-methylpentene, hexene, and octene; or a mixture thereof.
[0039] In particular, examples of the polyethylene include low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and high density polyethylene (HDPE). Among these, high density polyethylene, which has a high crystallinity and a high melting point of the resin, is most preferable.
[0040] The weight average molecular weight of the polyolefin may be 200,000 to 1,000,000, 220,000 to 700,000, or 250,000 to 500,000. In the present invention, a high molecular weight polyolefin having a weight average molecular weight of 200,000 to 1,000,000 is used as a starting material for producing a separation membrane, thereby ensuring the uniformity and membrane production process of the separation membrane film, and finally obtaining a separation membrane having excellent strength and heat resistance.
[0041] The diluent may be liquid or solid paraffin oil, wax, soybean oil, etc., which are commonly used in the manufacture of separation membranes. For example, the diluent may be a diluent capable of liquid-liquid phase separation with polyolefin. For example, it may be phthalates such as dibutyl phthalate, dihexyl phthalate, dioctyl phthalate, etc.; aromatic ethers such as diphenyl ether, benzyl ether, etc.; fatty acids having 10 to 20 carbon atoms such as palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, etc.; fatty alcohols having 10 to 20 carbon atoms such as palmitic alcohol, stearic alcohol, oleic alcohol, etc.; saturated and unsaturated fatty acids having a fatty acid group with 4 to 26 carbon atoms, such as palmitic acid mono-, di-, or triester, stearic acid mono-, di-, or triester, oleic acid mono-, di-, or triester, linoleic acid mono-, di-, or triester, and fatty acid esters in which one or more fatty acids in which the double bond of an unsaturated fatty acid is substituted with epoxy are ester-bonded with an alcohol having 1 to 8 hydroxyl groups and 1 to 10 carbon atoms. The diluent may be used alone or as a mixture containing two or more of the above-mentioned components.
[0042] The content of the diluent may be 100 parts by weight to 350 parts by weight, 125 parts by weight to 300 parts by weight, or 150 parts by weight to 250 parts by weight based on 100 parts by weight of the polyolefin. When the total content of the diluent satisfies the above numerical range, problems such as a decrease in porosity and a decrease in pore size, a significant decrease in permeability due to a decrease in interconnection between pores, an increase in viscosity of the polyolefin composition, and an increase in extrusion load, which makes processing difficult, due to a high polyolefin content, are reduced, and problems such as breakage and thickness variation during stretching due to a decrease in the kneadability of the polyolefin and the diluent due to a low polyolefin content are reduced, and polyolefin is extruded in a gel form without being thermodynamically kneaded with the diluent.
[0043] The polyolefin composition may further contain general additives for enhancing specific functions, such as initiators, crosslinking agents, catalytic agents, and oxidation stabilizers, as necessary.
[0044] The extrusion may be performed at a temperature in the range of 200° C. to 250° C. The extrusion may be performed using a conventional single-screw extruder or twin-screw extruder. For example, the extruder may be a twin-screw extruder equipped with a hopper for feeding the polyolefin and diluent, a kneading section for mixing the fed materials while transferring them, and a die outlet for extruding the mixed materials.
[0045] Next, in step (S2), the polyolefin composition is formed into a sheet and stretched.
[0046] In a specific embodiment of the present invention, the extruded polyolefin composition resulting from (S1) may be cooled and molded into a sheet by a general casting or calendaring method using water or air cooling.
[0047] In a specific embodiment of the present invention, the sheet-shaped product may be biaxially stretched in the machine direction and the transverse direction to form a stretched sheet. By stretching the sheet-shaped product, a separator having improved mechanical strength and puncture strength may be provided.
[0048] The stretching may be performed sequentially or simultaneously using a roll or tenter. The stretching ratio may be 3 times or more, or 4 to 10 times in each of the machine direction and the transverse direction. When the stretching ratio satisfies the above numerical range, it is possible to prevent the problem of the tensile strength and puncture strength being reduced due to the imbalance of physical properties in the machine direction and the transverse direction caused by insufficient orientation in one direction. In addition, when the total stretching ratio satisfies the above numerical range, it is possible to prevent the problem of no stretching or no formation of pores.
[0049] In one specific embodiment of the present invention, the stretching temperature may vary depending on the melting point of the polyolefin used, the concentration and type of diluent.
[0050] For example, when the polyolefin used is polyethylene and the diluent is liquid paraffin, the stretching temperature may be 70°C to 160°C, 90°C to 140°C, or 100°C to 130°C for longitudinal stretching (MD), and 90°C to 180°C, 110°C to 160°C, or 120°C to 150°C for transverse stretching (TD).
[0051] When the stretching temperature satisfies the above range, problems such as breakage or understretching due to insufficient flexibility caused by a low stretching temperature can be prevented, and partial overstretching or physical property differences caused by a high stretching temperature can be prevented.
[0052] Next, in step (S3), the stretched sheet is immersed in an extraction bath to prepare a porous membrane, the extraction bath containing an organic solvent in a lower layer and water and a surfactant in an upper layer.
[0053] In one embodiment of the present invention, a surfactant is included in the extraction tank for extracting the diluent, so that a separate additional process for introducing the surfactant into the separation membrane is not required, and therefore the surfactant can be introduced in a simpler manner.
[0054] In one specific embodiment of the present invention, the extraction tank has at least a two-layer structure divided into an upper layer and a lower layer.
[0055] Specifically, the lower layer of the extraction tank contains an organic solvent having a higher specific gravity than water, and the upper layer contains water and a surfactant, which acts as a water seal within the extraction tank to prevent the organic solvent from volatilizing.
[0056] The content ratio (or volume ratio) of the upper layer to the lower layer may be 1:99 to 10:90. By satisfying the above range, it is possible to ensure the dissolution time of the diluent through the organic solvent while suppressing the evaporation of the organic solvent in the lower layer.
[0057] In a specific embodiment of the present invention, the stretched sheet may pass through the lower layer first and then the upper layer in the extraction tank.
[0058] For example, the stretched sheet is first immersed in the lower part of an extraction tank to extract the diluent with an organic solvent, and then the sheet from which the diluent has been extracted passes through the upper part of the extraction tank to coat the sheet with a surfactant, followed by drying to produce a porous membrane.
[0059] The weight ratio of water to surfactant contained in the upper layer of the extraction tank may be 99.9:0.1 to 95:5, or 99.5:0.5 to 97:3. The weight ratio of water and surfactant contained in the above ranges is advantageous in that the surfactant remaining in the separation membrane can improve the hydrophilicity of the separation membrane while preventing mixing of the water in the upper layer with the organic solvent in the lower layer.
[0060] In a specific embodiment of the present invention, the surfactant may have a transmittance change rate before and after storage of the electrolyte of 70% or less, 10% to 70%, or 20% to 60%. Preferably, the surfactant may have a transmittance change rate before and after storage of the electrolyte of 20% to 50%.
[0061] When the transmittance change rate satisfies the above range, the surfactant can maintain stability even after the electrolyte is injected into the electrode assembly, and electrochemical side reactions can be suppressed, thereby improving the safety of the lithium secondary battery.
[0062] Permeability change rate (%) = [(Permeability before electrolyte storage - Permeability after electrolyte storage) / (Permeability before electrolyte storage)] × 100 ... Formula 1
[0063] In Equation 1, the permeability before storage of the electrolyte means the permeability measured immediately after adding a surfactant to the electrolyte, and the permeability after storage of the electrolyte means the permeability after adding a surfactant to the electrolyte and storing it at 70° C. for 3 hours. The electrolyte is a mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 7:3, and LiPF6 The surfactant is added in an amount of 1% by weight in 100% by weight of the electrolyte, and the transmittance of the electrolyte before and after storage is measured using an ultraviolet-visible spectrophotometer.
[0064] In the present invention, the transmittance can be measured using a UV-Vis spectrophotometer in accordance with ASTM-D1003.
[0065] In a specific embodiment of the present invention, the surfactant may be anionic, cationic, amphoteric, nonionic, etc., and one or more of these may be used in combination.
[0066] In a specific embodiment of the present invention, the organic solvent is not particularly limited as long as it can extract the diluent, but methylene chloride (MC), hexane (n-hexane), etc., which have high extraction efficiency and quick drying, can be used as the organic solvent. Considering the specific gravity with respect to water, it is preferable to use methylene chloride (MC) as the organic solvent.
[0067] In a specific embodiment of the present invention, the extraction method may be any of the common solvent extraction methods such as immersion, solvent spray, and ultrasonic methods, either individually or in combination. After the extraction process, the content of the residual diluent is preferably 1% by weight or less. If the content of the residual diluent exceeds 1% by weight, the physical properties are deteriorated and the permeability of the porous membrane is reduced. The content of the residual diluent may be affected by the extraction temperature and extraction time, and the extraction temperature is preferably high to increase the solubility of the diluent and the organic solvent, but is preferably 40° C. or less in consideration of safety issues caused by boiling of the organic solvent. If the extraction temperature is below the freezing point of the diluent, the extraction efficiency is significantly reduced, so the extraction temperature must be higher than the freezing point of the diluent.
[0068] The extraction time varies depending on the thickness of the porous membrane to be produced, but in the case of a porous membrane having a thickness of 5 μm to 15 μm, 2 to 4 minutes is appropriate.
[0069] Then, in step (S4), the porous membrane is heat-set.
[0070] The heat fixing is a method of fixing a porous membrane and applying heat to the membrane to forcibly fix the porous membrane that tends to shrink, thereby removing residual stress.
[0071] In a specific embodiment of the present invention, when the polyolefin is polyethylene, the heat setting temperature may be 120° C. to 150° C., 123° C. to 138° C., or 125° C. to 133° C. When the polyolefin is polyethylene, if the heat setting temperature satisfies the above numerical range, rearrangement of polyolefin molecules occurs, which can relieve residual stress in the porous membrane and reduce the problem of pore clogging in the porous membrane due to partial melting.
[0072] In a specific embodiment of the present invention, the time at the heat setting temperature may be 10 to 120 seconds, 20 to 90 seconds, or 30 to 60 seconds. When heat setting is performed for the above time, rearrangement of polyolefin molecules occurs, which can relieve residual stress in the porous membrane and reduce the problem of pore clogging in the porous membrane due to partial melting.
[0073] A polyolefin separation membrane according to another embodiment of the present invention is a separation membrane manufactured by a manufacturing method according to an embodiment of the present invention, and the separation membrane comprises a polyolefin porous support including a plurality of fibrils and a plurality of pores formed by the entanglement of the plurality of fibrils, and includes a surfactant on the surface of the fibrils.
[0074] The fibrils are formed by the polymer chains constituting the polyolefin porous support being stretched and oriented in the longitudinal direction during the manufacturing process of the polyolefin porous support, which increases the bonding strength between adjacent molecular chains and causes them to aggregate in the longitudinal direction. As a result, the polyolefin porous support has a structure in which a large number of fibrils arranged parallel to the surface of the substrate are laminated in layers. For the polyolefin porous support, the above-mentioned content of polyolefins can be referred to.
[0075] For the surfactant, the contents of the surfactant described above can be referred to.
[0076] In particular, in one specific embodiment of the present invention, by including a surfactant on the surface of the fibrils, the wettability of the electrolyte to the separator can be improved, and the occurrence of stains can be prevented, thereby suppressing poor appearance.
[0077] The polyolefin separation membrane according to an embodiment of the present invention may have a water contact angle of 100° or less. Specifically, since the polyolefin separation membrane according to the present invention has relatively improved hydrophilic properties, the polyolefin separation membrane may have a water contact angle in the range of 10° to 80°.
[0078] The water contact angle may be measured using a drop shape analyzer (DSA100S) manufactured by Kruss. Alternatively, for example, a drop of distilled water may be dropped on the surface of a polyolefin separation membrane, and the contact angle of the resulting drop may be measured using a contact angle meter model CA-DT-A (manufactured by Kyowa Interface Science Co., Ltd.) under conditions of 23°C and 50% RH. In this case, the contact angle may be measured at two points (left and right points) of each of the three sample films, and the average value of six measurements may be taken as the contact value. The diameter of the distilled water drop may be 2 mm, and the contact angle value displayed on the meter may be a value measured one minute after the drop of distilled water was dropped.
[0079] According to another embodiment of the present invention, there is provided an electrochemical device including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the separator being manufactured by the above-described method for manufacturing a separator.
[0080] Such electrochemical devices include all devices that perform electrochemical reactions, and specifically include all types of primary batteries, secondary batteries, fuel cells, solar cells, and capacitors such as supercapacitor devices, etc. In particular, among the secondary batteries, lithium secondary batteries including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, and lithium ion polymer secondary batteries are preferred.
[0081] The positive and negative electrodes to be used with the separator of the present invention are not particularly limited, and may be prepared by a conventional method known in the art in the form of an electrode active material bound to an electrode current collector. Non-limiting examples of the positive electrode active material among the electrode active materials include conventional positive electrode active materials used in the positive electrode of conventional electrochemical devices, and in particular, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, or a lithium composite oxide made by combining these materials. Non-limiting examples of the negative electrode active material include conventional negative electrode active materials used in the negative electrode of conventional electrochemical devices, and in particular, lithium metal or lithium alloys, carbon, petroleum coke, activated carbon, graphite, or other carbons, and other lithium adsorbents, and the like are preferred. Non-limiting examples of the positive electrode current collector include foils made of aluminum, nickel, or a combination thereof, and non-limiting examples of the negative electrode current collector include foils made of copper, gold, nickel, or a copper alloy, or a combination thereof.
[0082] The electrolyte used in the electrochemical element of the present invention is A + B - A salt having the structure: + Li + , Na + , K + or a combination thereof, - PF 6 - , B.F. 4- , Cl - , Br - , I - , ClO 4 - , AsF 6 - , C.H. 3 CO 2 - , C.F. 3 SO 3 - , N(CF 3 SO 2 ) 2 - , C(CF 2 SO 2 ) 3 - or a combination thereof, dissolved or dissociated in an organic solvent such as, but not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (γ-butyrolactone), or a mixture thereof.
[0083] The salt may be appropriately changed within a range that is generally usable, and the salt may be contained in the electrolyte at a concentration of 0.5 M to 2 M, specifically 0.9 M to 1.5 M. For example, a lithium salt may be used as the salt.
[0084] The electrolyte may be injected at an appropriate stage in the battery manufacturing process depending on the manufacturing process and desired properties of the final product, i.e., before battery assembly or at the final stage of battery assembly.
[0085] The present invention will be described in detail below with reference to specific examples. However, the examples according to the present invention can be modified into many other forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those skilled in the art.
[0086] [Example] The separation membranes of the respective Examples and Comparative Examples were produced by the following method.
[0087] <Example 1> A polyolefin composition was produced by extruding a mixture of high density polyethylene having a weight average molecular weight of 500,000 and liquid paraffin having a kinematic viscosity of 68.00 cSt in a weight ratio of 35:65 at 210°C.
[0088] The produced polyethylene composition was passed through a T-die and a cooled casting roll to form a sheet, which was then biaxially stretched in a sequential stretching machine at a stretching temperature of 115° C. and a stretch ratio of 7 times in both the longitudinal and transverse directions.
[0089] The stretched sheet was then immersed in an organic solvent by running it from the upper to the lower part of an extraction tank with a volume ratio of the upper to lower parts of 5:95, and after dwelling for 3 minutes, it was passed from the lower to the upper part, dried, and heat-set at 126°C to produce a porous membrane. Methylene chloride was added as an organic solvent to the lower part of the extraction tank, and water and a surfactant BYK333 (manufactured by BYK, polyether-modified polydimethylsiloxane) were added to the upper part of the extraction tank in a weight ratio of 98:2.
[0090] <Example 2> A separation membrane was produced in the same manner as in Example 1, except that WE3475 (BASF, sodium di-2-ethylhexyl sulfosuccinate) was introduced as a surfactant into the upper layer (water seal) of the extraction tank.
[0091] <Example 3> A separation membrane was produced in the same manner as in Example 1, except that KL245 (manufactured by TEGO, polyether-modified polysiloxane) was introduced as a surfactant into the upper layer (water seal) of the extraction tank.
[0092] <Comparative Example 1> A separation membrane was produced in the same manner as in Example 1, except that no surfactant was introduced into the upper layer (water seal) of the extraction tank.
[0093] <Comparative Example 2> A separation membrane was produced in the same manner as in Example 1, except that BYK347 (manufactured by BYK, polyether-modified siloxane) was introduced as a surfactant into the upper layer (water seal) of the extraction tank.
[0094] <Experimental Results> The transmittance change rate of the surfactants used in the examples of the present application was measured, and the results are shown in Table 1 below.
[0095] [Table 1]
[0096] <Method for measuring transmittance before / after electrolyte storage> LiPF 6 An electrolyte solution was prepared by dissolving the above to a concentration of 1.0 M. A surfactant was added to the electrolyte solution (100% by mass) at a content of 1% by mass, and the transmittance was measured using a UV-visible spectrophotometer in accordance with ASTM-D1003.
[0097] The transmittance before storage of the electrolyte was measured immediately after adding the surfactant to the electrolyte, and the transmittance after storage of the electrolyte was measured after adding the surfactant to the electrolyte and storing it at 70° C. for 3 hours.
[0098] Furthermore, in order to evaluate the impregnation of the separator with the electrolyte, 2 μl of propylene carbonate was dropped onto the separators produced in Examples 1 and 2 and Comparative Example 1, and the separators were observed after 5 minutes. The photographed images are shown in FIGS. 1 to 3.
[0099] The separation membranes prepared in the examples and comparative examples were evaluated for their physical properties as follows, and the results are shown in Table 2 below.
[0100] [Table 2]
[0101] (1) Appearance (water stains) evaluation method The appearance of the polyethylene separation membrane film was observed for water stains to judge whether it was a good product or not. (Judgment criteria: OK: no stains, NG: stains visible to the naked eye)
[0102] (2) Evaluation of battery cycle characteristics A secondary battery was manufactured by stacking the negative and positive electrodes alternately with the separators prepared in the examples and comparative examples interposed therebetween. 0.6 Mn 0.2 Co 0.2 ]O 2 Carbon black as a conductive material and polyvinylidene fluoride (PVdF) as a binder were mixed in a ratio of 97:1.5:1.5 to prepare a slurry, which was then coated on an aluminum foil with a thickness of 20μm, dried and pressed. The negative electrode was prepared by mixing a 5:5 mixture of artificial graphite and natural graphite as the negative electrode active material, Super C as a conductive material and SBR / CMC as a binder in a weight ratio of 98:1:1 to prepare a negative electrode slurry, which was then coated on one side of a copper current collector, dried and rolled.
[0103] The secondary batteries thus manufactured were initially charged and discharged once using an electrochemical charger / discharger. At this time, charging was performed by applying a current at a current density of 0.1C rate up to a voltage of 4.3V, and discharging was performed at the same current density up to 2.5V. This charging and discharging was performed a total of 200 times. The voltage and capacity of the positive and negative electrodes contained in each battery were measured during the above charging and discharging process. From these, the capacity retention rate of each battery was calculated as follows:
[0104] Capacity retention rate (%) = (Capacity after 200 cycles / Initial capacity) x 100 … Formula 2 (Criteria: OK: Capacity retention rate is 90% or more, NG: Capacity retention rate is less than 90%)
[0105] (3) Evaluation of water droplet contact angle of separation membrane The contact angle of the droplet formed by dropping a drop of distilled water onto the surface of the polyolefin separation membrane was measured using a contact angle meter model CA-DT-A (Kyowa Interface Science Co., Ltd.) under conditions of 23°C and 50% RH. The contact angle was measured at two points (left and right points) of each of the three sample films, and the average value of six measurements was taken as the contact value. The diameter of the drop of distilled water may be 2 mm, and the contact angle value displayed on the meter was measured one minute after the drop of distilled water was dropped.
Claims
1. (S1) mixing and extruding a polyolefin and a diluent to prepare a polyolefin composition; (S2) forming and stretching the polyolefin composition into a sheet; (S3) immersing the stretched sheet in an extraction bath to prepare a porous membrane; (S4) heat fixing the porous membrane; The method for producing a polyolefin separation membrane, wherein the extraction tank contains an organic solvent in a lower layer portion and water and a surfactant in an upper layer portion.
2. The surfactant has a transmittance change rate of 70% or less, and the transmittance change rate is expressed by the following formula 1: Permeability change rate (%) = [(permeability before storage of electrolyte solution - permeability after storage of electrolyte solution) / (permeability before storage of electrolyte solution)] × 100 ... Formula 1 is defined as In Equation 1, the permeability before storage of the electrolyte means the permeability measured immediately after adding a surfactant to the electrolyte, and the permeability after storage of the electrolyte means the permeability after adding a surfactant to the electrolyte and storing it at 70° C. for 3 hours. The electrolyte is a mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 7:3, and LiPF 6 The surfactant is added in an amount of 1% by mass in 100% by mass of the electrolyte, and the transmittance of the electrolyte before and after storage is measured using an ultraviolet-visible spectrophotometer in accordance with ASTM-D1003.
3. The method for producing a polyolefin separation membrane according to claim 1 , wherein the surfactant has a permeability change rate of 50% or less.
4. The method for producing a polyolefin separation membrane according to claim 1, wherein a weight ratio of the water to the surfactant is 99.9:0.1 to 95:
5.
5. The method for producing a polyolefin separation membrane according to claim 1 , wherein the organic solvent is methylene chloride.
6. The method for producing a polyolefin separation membrane according to claim 1 , wherein in step (S3), the stretched sheet passes through a lower layer portion first and then an upper layer portion in the extraction tank.
7. A polyolefin separation membrane produced by the method according to any one of claims 1 to 6.
8. A polyolefin porous support including a large number of fibrils and a large number of pores formed by the entanglement of a large number of the fibrils, The surfactant is included on the surface of the fibrils, The surfactant has a transmittance change rate before and after storage of the electrolyte of 70% or less, and the transmittance change rate is expressed by the following formula 1: Permeability change rate (%) = [(permeability before storage of electrolyte solution - permeability after storage of electrolyte solution) / (permeability before storage of electrolyte solution)] × 100 ... Formula 1 is defined as In Equation 1, the permeability before storage of the electrolyte means the permeability measured immediately after adding a surfactant to the electrolyte, and the permeability after storage of the electrolyte means the permeability after adding a surfactant to the electrolyte and storing it at 70° C. for 3 hours. The electrolyte is a mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 7:3, and LiPF 6 The surfactant is added in an amount of 1% by mass in 100% by mass of the electrolyte, and the permeability of the electrolyte before and after storage is measured using a haze meter in accordance with ASTM-D1003.
9. The polyolefin separation membrane according to claim 8 , wherein the surfactant has a permeability change rate before and after storage of an electrolyte of 50% or less.
10. The polyolefin separation membrane according to claim 8, wherein the polyolefin separation membrane has a water contact angle of 100° or less.
11. An electrochemical device comprising a positive electrode, a negative electrode, and the separator according to claim 8 interposed between the positive electrode and the negative electrode.
12. The electrochemical device according to claim 11, wherein the electrochemical device is a lithium secondary battery.
Citation Information
Patent Citations
Polyolefine microporous membrane and its manufacture, and separator using such membrane
JP1993094812A
Method for manufacturing separation membrane, separation membrane, and electrochemical battery
JP2014128791A
Lane painting device for repairing lanes and lane painting method using the same
KR102271994B1